SAFRANSKI, R. (2021). Hölderlin o el fuego divino de la poesía. Barcelona: Tusquets. - Ledesma de la Fuente, Álvaro (Daimon Revista Internacional de Filosofia, 2024)
Reseña de SAFRANSKI, R. (2021). Hölderlin o el fuego divino de la poesía. Barcelona: Tusquets.